A combined morphometric and phylogenetic revision of the Late Ordovician brachiopod genera Eochonetes and Thaerodonta. (14th September 2016) - Bauer, Jennifer E.; Stigall, Alycia L.
Abstract: Systematic revision of the Late Ordovician brachiopod genera Eochonetes Reed, 1917 and Thaerodonta Wang, 1949 was conducted utilizing specimen-based morphometric and species-level phylogenetic analyses. Previous studies had recognized Thaerodonta and Eochonetes as either distinct taxonomic entities or synonyms. New multivariate and phylogenetic analyses confirm the synonymy of Thaerodonta with Eochonetes and provide a framework to assess evolutionary and ecological patterns within the clade. Multivariate analyses were employed to delineate species in morphospace and provided information on potential species relationships. Phylogenetic analysis was used to produce an evolutionary framework for taxonomic revision and identify character evolution within the clade. Most species previously assigned to Thaerodonta are transferred to Eochonetes, and three others are excluded from Eochonetes and provisionally referred to other sowerbyellid genera. Three new species ( Eochonetes maearum new species, E. voldemortus new species, E. minerva new species) are described, one species ( Leptaena saxea Sardeson, 1892) is synonymized with E. recedens Sardeson, 1892, and one subspecies ( Thaerodonta mucronata scabra Howe, 1965) is rejected. This study demonstrates that a combination of complementary approaches and data types has the potential to advance interpretations beyond analyses confined to single analytical tools. Specifically, multivariate analyses provide constraints on species boundaries, whereas species-level phylogenetic analyses provide frameworks to examine morphological, ecological, and biogeographic evolution within a clade.